Mapping the process of product innovation: Contextualising the 'black box' of computer and video games design - Lake, Eric M. (Cranfield University, 2000)
The academic literature hitherto has mainly addressed the 'effects' of video games and not their creation. The thesis seeks to gain an understanding of the motivations behind the design choices in creating home computer and video games software in light of this 'gap'. The research sought to understand the process of constructing games by examining: (i) the individual designer's aims and how these were mediated by the contexts of. - (ii) the development team and organisation; (iii) the needs of the audience and their presence in the innovation process and (iv) the impact of the hardware manufacturer's quality assessment upon the game's design. These aims were met by outlining the industry structure operating in the video games' market from the period between the early 1980s to mid-1990s. This was performed with reference to the rise of Sega and Nintendo's hardware and software strategy, covering their diffusion from Japan to the US and UK. This highlighted the context surrounding the creation of three computer games from initial concept to actual commodity that served as the subject of case study analysis. The discussion seeks to explore the implications of the choices made in designing the games and widens the debate to the creation of other games. It is argued that the design of games mirrors aspects similar to the creation of other entertainment media but possess certain problems associated with aesthetic conventions, labour, industry and technical issues unique to this medium. Consequently the thesis outlines certain dimensions that impinge'upon the process of product innovation in entertainment software. From a theoretical perspective the application of a social constructivist approach to the emergence of a leisure technology is a novel one and demonstrates the contingent nature of game design.